SOME OBSERVATIONS ON POLLUTION OF THE SUV AON STREAM BY THE EFFLUENTS OF A SUGAR FACTORY, BALRAMPUR (U.P.) - Banerjea, Santimoy; Motwani, M P (Indian Journal of Fisheries, 2015)
In the earlier publication which was first in the series, Motwani et al. (1956) had emphasised importance of the problem of pollution in India and they recommended that the waste disposal problem must be pursued with due consideration to the utilisation of fishery resources of our national waterways. Like most industries, cane sugar factories have waste materials which if permitted to enter a stream can do much to alter the physical, chemical and biological properties of the receiving waters. Washings from sugarcane, pulp press and condensers, lime-cake slurry, molasses and oH from machineries are some of the more common types of wastes from a sugar factory and these may contain a number of inorganic and organic compounds some of which may produce toxic substances by decomposition and others which may alter or influence the natural regimen of the conditions of existence.